Application of aerosol optical properties to estimate aerosol type from ground-based remote sensing observation at urban area of northeastern China. (September 2015) - Che, Huizheng; Zhao, Hujia; Wu, Yunfei; Xia, Xiangao; Zhu, Jun; Dubovik, Oleg; Estelles, Victor; Ma, Yanjun; Wang, Yangfeng; Wang, Hong; Wang, Yaqiang; Zhang, Xiaoye; et al.
Abstract: Aerosol optical properties were derived from ground-based sunphotometer observations between 2009-2013 at three urban sites of Shenyang, Anshan, Fushun in northeastern China. The annual means for extinction aerosol optical depths (EAOD) at 500 nm were 0.57±0.38, 0.52±0.35, and 0.41±0.31 at Shenyang, Anshan, Fushun, respectively. The corresponding annual means for the extinction Angstrom exponents (EAE) computed for the wavelengths of 440 and 870 nm were 0.86±0.32, 0.86±0.34 and 0.91±0.35, respectively, indicating that urban area of Northeast China were affected by both coarse and fine particles. Hygroscopic growth in summer and incursions of dust aerosols in spring were evidently revealed from the analysis of the relationship between EAE and δ EAE (the EAE difference, δ EAE=EAE(440, 670)−EAE(670, 870)). The annual mean absorption aerosol optical depths (AAOD440 nm ) values at Shenyang, Anshan, Fushun were 0.15±0.11, 0.10±0.07, 0.08±0.04, respectively. The annual mean absorption Angstrom exponents (AAE440–870 nm ) values were 0.86±0.24, 1.19±0.39, 1.33±0.36 at Shenyang, Anshan, Fushun, respectively. When the AAEs were close to unity at Anshan, the absorption aerosol particles evidently consisted of black carbon from coal combustion and motor vehicles. Larger AAEs at Fushun were indicative of absorbing aerosols mainly from biomass burning and mineral dust. The AAE at Shenyang was<1 which may be consistent with black carbon particles with absorbing or non-absorbing coatings. Analysis of the relationship between the AAEs and extinction Angstrom exponents showed that the aerosol populations at these three sites could be classified as "mixed-small particles" including anthropogenic particles and secondary organic aerosol with highly variable sphericity fractions. Highlights: It identified aerosol type and mixing state in northeastern China (NEC); Hydroscopic growth and incursions of dust aerosols were evidently revealed in NEC; Aerosol mixing state in NEC can be classified as "mixed-small particles" mainly.